Ab Initio Modeling of CuGa1−xInxS2, CuGaS2(1−x)Se2x and Ag1−xCuxGaS2 Chalcopyrite Solid Solutions for Photovoltaic Applications - Grechenkov, Jurij; Gopejenko, Aleksejs; Bocharov, Dmitry; Isakoviča, Inta; Popov, Anatoli I.; Brik, Mikhail G.; Piskunov, Sergei (MDPI, 2023)
Chalcopyrites are ternary semiconductor compounds with successful applications in photovoltaics. Certain chalcopyrites are well researched, yet others remain understudied despite showing promise. In this study, we use ab initio methods to study CuGaS2, AgGaS2, and CuGaSe2 chalcopyrites with a focus on their less studied solid solutions. We use density functional theory (DFT) to study the effects that atomic configurations have on the properties of a solid solution and we calculate the optical absorption spectra using a many-body perturbation theory. Our theoretical simulations predict that excess of In and Se in the solid solutions leads to narrowing of the band gap and to the broadening of the absorption spectra. Obtained results show promise for possible photovoltaic applications, as well as developed methodology can be used for further study of other promising chalcopyritic compounds. © 2023 by the authors. --//-- Grechenkov J., Gopejenko A., Bocharov D., Isakoviča I., Popov A.I., Brik M.G., Piskunov S.; Ab Initio Modeling of CuGa1−xInxS2, CuGaS2(1−x)Se2x and Ag1−xCuxGaS2 Chalcopyrite Solid Solutions for Photovoltaic Applications; (2023) Energies, 16 (12), art. no. 4823; DOI: 10.3390/en16124823; https://www.scopus.com/inward/record.uri?eid=2-s2.0-85163833999&doi=10.3390%2fen16124823&partnerID=40&md5=b9a4e3df89ff3bf5acdeda068fe29f6c
This research is funded by the Latvian Council of Science grant No. LZP-2021/1-0322 (Large-scale computer modelling of defective ternary chalcopyrites for photovoltaic applications). All calculations were performed on Latvian Supercomputer Cluster (LASC) located at Institute of Solid State Physics in Riga. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2. M.G.B. also acknowledges the funding from Ministry of Science, Technological Development, and Innovation of the Republic of Serbia (451-03-47/2023-01/200017).
Keywords: Research Subject Categories::NATURAL SCIENCES; ab initio calculation; chalcopyrites; density functional theory; photovoltaics; solid solutions